MENUJU KEBUDAYAAN - Paulus Satyo Istandar Tan (LPPM Politeknik Saint Paul Sorong, 2020)
The research method used is a qualitative description method by collecting library data, reading and recording and processing research materials. Culture, in short, is the creation, control and processing of human values. It involves humanizing raw natural materials and their results. In the material nature, the nature of the self and the natural environment both physical and social, values are identified and developed so that they are perfect. Cultivating nature, humanizing life, perfecting human relations is an inseparable unity.